T33. NEUROIMMUNE MECHANISMS OF PSYCHIATRIC DISORDERS: LONGITUDINAL EVALUATION OF DIFFUSION MEASURES OF EXTRACELLULAR FREE WATER IN A NON-HUMAN PRIMATE MODEL OF MATERNAL IMMUNE ACTIVATION. (18th May 2020) - Carter, Cameron; Lesh, Tyler; Iosef, Ana-Maria; Tanase, Costin; Vaslova, Rosa; Styner, Martin; Maddock, Richard; Bauman, Melissa
Abstract: Background: A key finding in developmental neurobiology is a widespread role for immune molecules in normal brain development and synaptic function and evidence has been accumulating for an immune-based developmental pathophysiology in psychiatric disorders, particularly in schizophrenia. Epidemiological studies have revealed an increased incidence of schizophrenia in offspring of mothers who had an infection during pregnancy while GWAS studies have identified genetic links to the major histocompatibility complex and peripheral changes in immune markers are widely reported in the illness. The murine maternal immune activation model system is widely used to investigate the effects of immune activation during pregnancy on brain development in behavior in offspring. Here we report findings from an ongoing study of a unique cohort on non-human primates (NHP) who underwent MIA (compared to controls) on a promising biomarker of neuroimmune perturbation in vivo–extracellular free water–a diffusion magnetic resonance imaging measure obtained with a multi-shell acquisition, which we have shown in multiple studies to be increased in young people with early psychosis. Methods: Fourteen pregnant rhesus monkeys (Macaca mulatta) received polyICLC and 14 control animals have been scanned prospectively from both to their current age of 3.5 years. The offspring from both groups underwent a diffusion MRI scan on a 3 Tesla Siemens Skyra scanner in which multiple b-value shells were acquired to improve estimation of extracellular free water. Data were collected when the offspring were 1, 6, 12, 24 and 36 months to date. Diffusion images were nonlinearly aligned to individual subject MPRAGE scans, which were segmented and parcellated into regions of interest using multi-atlas techniques. For this preliminary analysis, frontal, cingulate, and temporo-limbic regions were selected as a priori ROIs in addition to whole-brain gray and white matter masks. Group differences were assessed using repeated measures ANOVA and independent samples t-tests. Results: Results from birth to age 2 years showed a significant main effect of group in both white (p<.05) and gray (p<.001) cingulate cortex free water, with MIA-exposed offspring showing higher free water. Similar trends were also identified in prefrontal white matter free water (p=.07) and whole-brain white (p=.11) and gray matter free water (p=.07). No significant group by time interactions were identified. Data analysis is currently underway including the 3-year time point. Discussion: Despite the lack of gross behavioral abnormalities at age 2, extracellular free water values are increased in MIA-exposed offspring, particularly in the cingulate cortex. More global whole-brain free water group differences, however, did not reach statistical significance, which may indicate some regional specificity to these changes early in development. These NHP MIA model complement the human schizophrenia literature in which extracellular free water increases have been repeatedly identified. And show that changes in the brain occur early in life, well before the emergence of atypical behaviors in the NHP model.